Analisis Antropometri dan Physical Fitness terhadap Performa Atlet Kayak Kabupaten Bandung - Rania Ragil Pangestu; Dede Rohmat Nurjaya; Yadi Sunaryadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the relationship between anthropometric characteristics and physical fitness and the performance of kayaking athletes in the 200 m, 500 m, and 1000 m events in Bandung Regency. This research employed a descriptive correlational method with a quantitative approach involving 15 athletes selected through purposive sampling. Anthropometric variables included height, body weight, sitting height, body mass index (BMI), body fat percentage, and muscle mass. Physical fitness variables consisted of the Overhead Medicine Ball Throw (OMBT), Vertical Jump (VJ), Sit and Reach (SR), and the Cooper run test. The results showed that in male athletes, physical fitness and body composition had a significant relationship with performance, while in female athletes explosive strength and body composition were significantly associated with performance. These findings highlight the importance of developing optimal body composition and muscle strength in kayak athlete training programs. Keywords : Antropometri, Athlete Performance, Physical Fitness, Sprint Kayaking